Konsolidacja autorytaryzmu w Egipcie po 2013 roku (Politeja, 2025)
THE CONSOLIDATION OF AUTHORITARIANISM IN EGYPT AFTER 2013This study examines the process of authoritarian consolidation in Egypt from 2013 to 2023, analyzing the transformation of the political system under Sisi. Utilizing Juan J. Linz and Alfred Stepan’s framework of five arenas of democratic consolidation, the research investigates how these arenas have been reconfigured to strengthen authoritarian control. The analysis reveals systematic changes across all spheres: the rule of law has been undermined through constitutional amendments and restrictive legislation; the state apparatus has been recentralized with the military and security aparatus; civil society has been severely constrained through legal and administrative measures; the political society has been reshaped to marginalize opposition and promote pro-regime parties; and the economic society has witnessed increased military involvement in key sectors. Key findings highlight the regime’s use of legal mechanisms to legitimize authoritarian practices, the marginalization of independent political and civil society actors, and the military’s expanding role in both politics and the economy. The study concludes that Egypt has evolved into a hybrid regime where democratic institutions exist but are largely subordinated to executive power, with the military playing a central role in maintaining regime stability.